STRUCTURAL TRANSFORMATİON OF THE SUPERVİSİON PROCESS İN THE TURKİSH EDUCATİON SYSTEM (Third Sector Social Economic Review, 2024)
In this study, it is aimed to analyze the structural changes made in the field of educational supervision, in order to reveal the current situation and to develop suggestions in line with the criticized issues regarding the changes implemented by legal regulations.This research, which aims to examine the transformation in the supervision structure of the Turkish Education System with the legal regulations regarding education supervision in 2011, 2014, 2016, 2017, 2018 and the following years, is a qualitative research and the collection and analysis of data was designed in the document scanning model.In line with the research, it was tried to reach the primary sources, legislation, regulations, laws and decree-laws, directives related to educational supervision between the years 2011-2022 were scanned and analyzed comparatively.As a result of the research, it was concluded that despite the numerous regulations made in the last ten years, the regulations remained in the formal dimension and the regulations aimed at increasing the functionality of the educational supervision did not take place.
Keywords: educational supervision; control system in education; education inspector; education superintendent